Pembagian Waris Receptie Exit: Tinjauan Kritis Terhadap Pemikiran Hazairin - anggoro, sandiko yudho; Lahuri, Setiawan Bin; Zarkasyi, Muhammad Ridlo (Istinbath : Jurnal Hukum, 2022)
Hazairin as master on Indonesian’s traditions law proffer a device for implementing Islamic law by introduce receptie exit theory. He said, an Islamic inheritance law is not only hegemonized by Indonesian culture, but also by Arab culture which has a patrilineal system. Furthemore, he explained that the Islamic inheritance law does not interpret the Qur'an justice which is actually bilateral. So Hazairin created a new concept regarding of inheritance law. The purpose of this study is to explain that the Islamic inheritance is accordance with the Qur'an. Islamic inheritance law has a universal justice, because it’s inculde theological, maslahah, social and economic aspects. Thus, Hazairin’s concept does not only criticize of ulama ideas, In fact he deconstructs Islamic inheritance law where he negates ashaba, abolishes dzawu al-arḥam, and reconstructs the concept of hijab.